Penerapan model pembelajaran kooperatif tipe think pair share untuk meningkatkan pemahaman konsep kegiatan ekonomi dan jenis-jenis usaha di indonesia pada peserta didik kelas v sekolah dasar - Radhita Tika Sari; Siti Istiyati; Riyadi Riyadi (Didaktika Dwija Indria, 2019)
The purpose of this thorough to improving the conceptual understanding of economic activities and kind of business in Indonesia for fifth grade students of SD N 03 Karanganyar in the 2018/2019 academic year using cooperative learning type Think Pair Share. This classroom action research consist of two cycles, each cycle includes two meeting. Subject and sorce data in this thorough were teacher and students of V SD N 03 Karanganyar. The thorough uses collection and teachnique through observation, interviews, test, and documentation. The data validity used in content validation. The data analysis teachnique used is an interactive analysis model. The conclusion in this research are cooperative learning type TPS that can improve the concept understanding of economic activities and types of business in Indonesiafor fifth grade students of SD N 03 Karanganyar in the academic year 2018/2019.